-2(a+1)-3(1-7a)=-24

Simple and best practice solution for -2(a+1)-3(1-7a)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(a+1)-3(1-7a)=-24 equation:


Simplifying
-2(a + 1) + -3(1 + -7a) = -24

Reorder the terms:
-2(1 + a) + -3(1 + -7a) = -24
(1 * -2 + a * -2) + -3(1 + -7a) = -24
(-2 + -2a) + -3(1 + -7a) = -24
-2 + -2a + (1 * -3 + -7a * -3) = -24
-2 + -2a + (-3 + 21a) = -24

Reorder the terms:
-2 + -3 + -2a + 21a = -24

Combine like terms: -2 + -3 = -5
-5 + -2a + 21a = -24

Combine like terms: -2a + 21a = 19a
-5 + 19a = -24

Solving
-5 + 19a = -24

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 19a = -24 + 5

Combine like terms: -5 + 5 = 0
0 + 19a = -24 + 5
19a = -24 + 5

Combine like terms: -24 + 5 = -19
19a = -19

Divide each side by '19'.
a = -1

Simplifying
a = -1

See similar equations:

| 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 | | -1+5(x+2)=12x+3-1x | | 3y^4-13y^2-10=0 | | 28+2x-1=3x+22 | | 19.5(13.3-4.4x)=7.2(0.8x-116) | | 4(5t+10)= | | t^4+21t^2+20=0 | | t^4+21lt^2+20=0 | | 6z-12= | | 4(3x-1P)=2(x+3) | | 4(a+2)-9=11 | | 3m-2=8 | | sqrt(3x)+1=x+1 | | t^4+2lt^2+20=0 | | -4(y+3)-2y=24 | | 2x^2+170=0 | | -9(x+3)+4x=-2 | | 11x^4+21x^3-35x^2-63x+6=0 | | 8(6n+10)+6n= |

Equations solver categories